Going back to the roots of W.A. Shewhart (and further) and introduction of a new CPD cycle. Issue 1 (4th January 2017) - Saier, Martin Christopher
Abstract : Purpose: Investigating the beginning of project management (app. 30 BC) with a focus on business models similar to the "PDCA" cycle, the purpose of this paper is to find an approach which could be used as a new standard procedure for the eradication of projects in Lean project management. Design/methodology/approach: Based on literature research of models similar to Walter A. Shehwart's three-step and Edward W. Deming's four-step (PDC(A)) wheel, the investigated models are interconnected to form a new concept which represents an innovative cycle logic proposed to be applied in Lean project management. This new cycle logic is rolled out on three different levels, which are transferred from the Lean management hoshin kanri model to Lean project management. In addition to literature research, semi-structured interviews were performed to get an indication as to the integration of Lean management (with a focus on PDCA) in project management today. Findings: It was found that the "Check Plan Do" cycle is a Lean variant of the "Plan Do Check Act" model that is already used in consulting projects in practice, partially appears in project management standards, in governance models of ambulance, fire services, human aid and military forces and in quality management models of Six Sigma, design for Six Sigma and an excellence model of the European Foundation for Quality Management. To ensure continuous improvement it was found that the new CPD cycle can be used on different "planning" levels in analogy to the hoshin kanri logic. Originality/value: To the best of the author's knowledge, a discussion as to how the PDCA cycle can be adapted to Lean project management, considering the implication of business models similar to the PDCA wheel, has not yet been conducted within the field of project management.